2003
DOI: 10.2174/1568026033452393
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanotechnologies for Studying Cellular Function

Abstract: The study of complex biological systems requires methods to perturb the system in complex yet controlled ways to elucidate mechanisms and dynamic interactions, and to recreate in vivo conditions in flexible in vitro set-ups. This paper reviews recent advances in the use of micro- and nanotechnologies in the study of complex biological systems and the advantages they provide in these two areas. Particularly useful for controlling the chemical and mechanical microenvironments of cells is a set of techniques call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Microfluidic devices were fabricated using standard soft lithography methods (30,35,38) . Approximately 2 ml of selected negative-tone photoresist (SU-8, MicroChem, Newton, MA) was dispensed onto the wafer on a spinner.…”
Section: Vol 71 2005 Mobility Of Protozoa Through Narrow Channels 4629mentioning
confidence: 99%
“…Microfluidic devices were fabricated using standard soft lithography methods (30,35,38) . Approximately 2 ml of selected negative-tone photoresist (SU-8, MicroChem, Newton, MA) was dispensed onto the wafer on a spinner.…”
Section: Vol 71 2005 Mobility Of Protozoa Through Narrow Channels 4629mentioning
confidence: 99%
“…To record metabolic changes of a small number or single cells it is necessary to scale down the cell culture volume and the sensor size and provide fluidic access to the cell culture volume for perfusion and toxin delivery (Shim et al, 2003). Recently, microfabrication and microfluidic technologies have been utilized to develop lab-on-a-chip devices for cell analysis in which the extracellular volume and the sensor size is smaller than or comparable to the cell size approaching in vivo conditions (Cheng et al, 2006;Ganitkevich et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Such differences will be advantageous for enhanced autocrine and paracrine effects, for example, and are expected to affect cell function. [2,3,44] …”
Section: Full Papermentioning
confidence: 99%
“…These components present the cells with biochemical signals, and the cells are continually faced with sensing these inputs, processing the signals through signal transduction and gene regulation networks, and executing cell behavioral or fate choices. [1,2] Two of the most important microenvironment components are oxygen concentrations and the extracellular matrix (ECM). Recently, we demonstrated that oxygen concentrations can be regulated in microfluidic bioreactors made of poly(dimethylsiloxane) (PDMS).…”
Section: Introductionmentioning
confidence: 99%